Meeting the challenges in conducting research in vulnerable older adults with self-neglect-notes from a field team - Pickens, Sabrina; Burnett, Jason; Trail Ross, Mary Ellen; Jones, Erick; Jefferson, Felicia (Frontiers in Medicine, 2023)
Gaining a systematic understanding of possible ways to increase the quality and lifespan of older adults experiencing self-neglect has unique challenges. These challenges include identifying self-neglect in the community and navigating levels of cognitive, physical, and/or psychological difficulties in this population that impact recruitment, consent, and accurate data collection. Conducting quality research under some of the environmental self-neglect conditions such as squalor, animal and insect infestations and no utilities can also challenge planned study protocols and study validity. This manuscript presents details of these overarching challenges and some of the workable solutions noted and implemented by research field-team members who have enrolled over 300 adults experiencing self-neglect for various studies. Usual research methodology must overcome these barriers to work to create consciousness about the self-neglect population. The classic series of cases is still a good alternative when describing self-neglect. Considerations for conducting future self-neglect research are presented.